A qualitative analysis on a Nicholson-Bailey Host-Parasitoid Model - Tolomia, Angeli Joyce A.; Almocera, Lorna S. (Cebu City College of Science, University of the Philippines Cebu, 2019)
Many ecological models have been studied in the recent years, because of their wide applicability to population dynamics. In the case of discrete dynamical system, one has more efficient computational results for numerical simulations and has rich dynamics as compared to continuous system. Several papers have been published about mathematical models of biology that discuss the system of difference equations generated from system of differential equations as well as numerical methods. In mathematical biology, Host-Parasitoid models have attracted many researchers because of its characteristic and behavior. They believe that the positive locally asymptotically stable equilibrium points this model has, is very important in an ecological system.
Thesis (Bachelor of Science in Mathematics). University of the Philippines Cebu. June 2019.